The Influence of Work Flexibility and Self Efficacy on Employee Performance in Bekasi District - Dewi, Indah Astuti (Lentera Ilmu Nusantara, 2024)
This research aims to analyze the influence of work flexibility and self-efficacy on employee performance among employees who work in the Bekasi Regency area. Work flexibility and self-efficacy are independent variables, while the dependent variable is employee performance which is measured using a Likert scale with an interval scale type. Sampling was carried out in the Bekasi Regency area using the method of distributing questionnaires containing statements regarding the influence of work flexibility and self-efficacy on employee performance. The results of this research found that the influence of work flexibility has a positive effect on employee performance and self-efficacy does not have a positive effect on employee performance.